Copper and cobalt co-catalyzed aerobic oxidative cross-dehydrogenative coupling reaction of (benzo)azoles. Issue 21 (11th September 2019) - Li, Yanrong; Qian, Fen; Ge, Xia; Liu, Tao; Jalani, Hitesh B.; Lu, Hongjian; Li, Guigen
Abstract : The dehydrogenative cross-coupling (CDC) reaction of diversely substituted azoles was realized by copper and cobalt co-catalysis under air conditions. Abstract : The dehydrogenative cross-coupling (CDC) reaction of diversely substituted azoles, synergistically catalyzed by copper and cobalt, is reported. This protocol represents the first example of the use of air as an oxidant to carry out this chemical reaction. The process provides a convenient and economical method for the construction of valuable unsymmetrical bis-heteroaryl compounds, including bis-benzoazole compounds that were not obtained in previous catalytic CDC reactions.